2011
DOI: 10.5324/nje.v21i1.1425
|View full text |Cite
|
Sign up to set email alerts
|

Can the use of psychoactive drugs in the general adult population be estimated based on data from a roadside survey of drugs and driving?

Abstract: A roadside survey of drugs and driving was performed in south-eastern Norway in 2005-6. Samples of saliva from a total of 10,503 drivers above 20 years of age were analysed, and the results were weighted for under-and over-sampling compared to the population distribution in the study area. Weighted results were compared with data on dispensed prescriptions of zopiclone, codeine and diazepam at Norwegian pharmacies in the same area and with self-reported use of cannabis. When using roadside data to estimate dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…As expected [4,28], the younger employees had a higher alcohol consumption than the older employees, but medicinal drug use was more frequent among older employees than among younger employees. Similar results have been reported by Skretting et al , Gjerde et al and Nesvåg and Lie [13,15,16]. Self-reported in-efficiency or hangover at work due to alcohol during the past 12 months was more frequent among the age group below 40 years and among employees with higher educational level, and the results were consistent with data published by Storvoll et al [17].…”
Section: Discussionsupporting
confidence: 92%
“…As expected [4,28], the younger employees had a higher alcohol consumption than the older employees, but medicinal drug use was more frequent among older employees than among younger employees. Similar results have been reported by Skretting et al , Gjerde et al and Nesvåg and Lie [13,15,16]. Self-reported in-efficiency or hangover at work due to alcohol during the past 12 months was more frequent among the age group below 40 years and among employees with higher educational level, and the results were consistent with data published by Storvoll et al [17].…”
Section: Discussionsupporting
confidence: 92%
“…Under-reporting is not unexpected in the survey questionnaires because the subject was drug use and the level of response was low, but this discrepancy may be even larger than is immediately apparent from the present study. An earlier roadside study49 found that the use of medicinal drugs was underestimated by 17–59% when using data from a survey of drivers compared with actually dispensed amounts in the studied area. For the use of cannabis the results from a roadside survey were similar to self-reported data.…”
Section: Discussionmentioning
confidence: 85%